PERAN GURU DALAM PENGUATAN KEMAMPUAN SOSIAL BERBASIS NILAI-NILAI ISLAM PERSPEKTIF IMAM AL-GHAZALI PADA SISWA KELAS 1 MI HASYIMIYAH SUKOLILO TUBAN TAHUN PELAJARAN 2025/2026 - Kamilah, Arina; Ghofir, Jamal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of teachers in strengthening social skills based on Islamic values ​​from the perspective of Imam Al-Ghazali in grade 1 students of MI Hasyimiyah Sukolilo Tuban in the 2025/2026 academic year. Elementary school students' social skills are an important aspect in supporting the process of adaptation and interaction in the school environment, especially in developing cooperation, empathy, and positive social interactions. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of class teachers and several grade 1 students out of 20 students as research subjects. The results of the study indicate that students' social adaptation skills since the beginning of school are classified as good and develop gradually through the habituation of Islamic values ​​such as mutual assistance (ta'awun), compassion (rahmah), and mutual respect instilled by teachers through advice methods, role models, and direct practice in daily learning activities. Teachers act as educators, guides, motivators, facilitators, and role models in instilling Islamic values ​​so as to strengthen students' ability to cooperate, empathize, and interact socially in a sustainable manner in accordance with Imam Al-Ghazali's educational perspective.